Can we make money with fifth-order autocorrelation in Japanese stock prices? - Yoshiro Tsutsui; Kenjiro Hirayama; Takahiro Tanaka; Nobutaka Uesugi (Osaka University, Institute of Social and Economic Research (ISER), 2005)
We first report that one-minute returns on TOPIX have exhibited significant autocorrelation at five-minute intervals since 1997/98, which implies there is an arbitrage opportunity. Special quotes that are issued whenever there is a price jump in excess of a predetermined band seem to be the source of this autocorrelation, since these have been updated at five-minute intervals since August 1998. Individual stock returns also exhibit fifth-order autocorrelation, but this disappears when the data with special quotes are excluded from the sample. The arbitrage opportunities, however, turn out to be spurious since trading is suspended whenever a special quote is issued.
Keywords: G14; 330; stock prices; autocorrelation; efficient market hypothesis; Japan; Börsenkurs; Arbitrage Pricing; Japan; Effizienzmarkthypothese; Autokorrelation